Assessing the Performance of the De Novo Postoperative Stress Urinary Incontinence Calculator. Issue 4 (April 2021) - Ross, James H.; Carter-Brooks, Charelle M.; Ruppert, Kristine M.; Giugale, Lauren E.; Shepherd, Jonathan P.; Zyczynski, Halina M.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:23–27) In recent years, the evidence-based recommendation that a prophylactic incontinence procedure be performed at the time of advanced prolapse surgery (to reduce the incidence of de novo stress urinary incontinence [SUI]) has been challenged. Reduction stress testing and surgeon's judgment may be unreliable, further challenging benefits of a prophylactic concomitant incontinence procedure.